Developing a management strategy to reduce roof rat, Rattus rattus, impacts on open-cup nesting songbirds in California riparian forests - Whisson, Desley A.; Quinn, Jessica H.; Collins, Kellie; Engilis , Andrew Jr. (eScholarship, University of California, 2004)
In 2001, roof rats were identified as major predators of open-cup songbird nests in old growth riparian forests of California’s Central Valley. Nest predation was as high as 80%. For some bird species in recent years, the populations had declined, and their range was reduced. A management strategy to reduce rat impacts on songbirds was considered a priority. Following a review of the literature and consultation with land managers and experts in rodent management and bird conservation, we decided to reduce rat populations with poison baits delivered in bait stations immediately prior to the songbird nesting period. We subsequently conducted studies to provide information on rat home range and habitat use, potential baits, optimal bait station placement and distribution, and the potential non-target hazards of the program. The management strategy was then implemented in one riparian forest tract in October - December 2003. This is an adaptive management approach that will be evaluated in 2004, modified as necessary, and if successful, potentially applied to other riparian forests. In this paper we describe our approach to developing the management strategy, provide preliminary results, and discuss some of the potential problems with its implementation on a large scale.